Business Strategy and Enterprise Modeling: Nokia Case Study - Alanudin, Dian; Salikha, Laura Nanda (CV. Publikasi Indonesia, 2024)
This study aims to analyze the main causes of Nokia's market share decline and formulate recovery strategies using the PESTEL framework, Porter’s Five Forces analysis, and SWOT. The research adopts a case study method, collecting data from Nokia’s financial reports, industry reports, and relevant academic literature. Key findings reveal that Nokia’s delayed adoption of smartphone technology and internal management conflicts significantly contributed to the company’s downfall. Additionally, the PESTEL analysis highlights external challenges such as shifting consumer preferences and intense technological competition. Based on the analysis, strategic recommendations include adopting a Blue Ocean strategy, internal restructuring, and enhancing technological innovation to regain Nokia's competitive advantage. This research provides valuable insights into how technology companies can avoid decline in rapidly changing industries.